PENGARUH MODAL, TEKNOLOGI DAN KEWIRAUSAHAAN TERHADAP NILAI PRODUKSI DAN PENDAPATAN INDUSTRI PAKAIAN JADI - Wira Putra, I Wayan; Jember, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.09.TAHUN 2019DO - 10.24843/EEB.2019.v08.i09.p01, 2019)
The objectives to be achieved in this study, among others, are to determine the effect of capital, technology, entrepreneurship, and production value on the income of the apparel industry in Karangasem Regency. This research was conducted in Karangasem Regency, with business units totaling 30 business units. The method of determining the sample used is the Total Sampling method, which is a sampling technique in which all members of the population are sampled. Data analysis techniques used are path analysis techniques to determine the direct and indirect effects of capital, technology, and entrepreneurship on the value of production and income. Based on the results of the study, it is known that the capital, entrepreneurship, and production value variables have a positive and significant effect on the income of the apparel industry in Karangasem Regency. Meanwhile, the technology variable does not affect the income of the apparel industry in Karangasem Regency. From the calculation of the sobel test, it is known that the variable value of production mediates the variables of capital and entrepreneurship on the income of the apparel industry in Karangasem Regency